Case Report: A new noninvasive device-based treatment of a mesencephalic H3 K27M glioma - Helekar, Santosh A.; Ijare, Omkar B.; Sharpe, Martyn A.; Pichumani, Kumar; Baskin, David S. (Frontiers in Oncology, 2025)
Brainstem gliomas have a poor prognosis and ineffective therapeutic options. We have developed a noninvasive device called an Oncomagnetic device that produces selective oncolysis of gliomas in vitro and marked reduction of contrast-enhanced tumor (CET) volume in end-stage recurrent glioblastoma (GBM) patients. Here we report Oncomagnetic treatment (OMT) of a 28-year-old woman who had undergone partial surgical excision and radiotherapy of a H3 K27M midline glioma in the mesencephalon and pons. OMT initiated after the first recurrence of the tumor was well tolerated for more than 694 days by the patient. There was near-complete regression of the CET at 145 days with symptomatic relief and a partial regression at 554 days after an apparent progression at 518 days. OMT was discontinued after 694 days because of hospital admission due to injuries from a fall and disease progression, which then led to her death. These findings demonstrate the potential of a new effective, nontoxic, and noninvasive wearable device-based treatment for the deadly diffuse midline glioma.